The Effectiveness of SIMENIK (Electronic Media System) in Stunting Reduction Efforts in Pitu District, Ngawi Regency - Puji Astuti; Veny Ari Sejati; Maria Magdalena Widiantari (International Journal of Management Science and Information Technology, 2026)
Stunting is a serious public health issue in Indonesia, including in Pitu Subdistrict, Ngawi Regency. Stunting is caused by multifactorial factors, such as chronic malnutrition, recurrent infections, poor sanitation, and low parental knowledge about child nutrition (Beal et al., n.d.). Ministry of Health of the Republic of Indonesia, 2022). One approach to address stunting is the utilization of information technology, such as SIMENIK (Electronic Media System), which is designed to disseminate health information, monitor child nutritional status, and support community nutrition interventions (World Health Organization, n.d.). This study aims to analyze the effectiveness of SIMENIK in supporting stunting reduction in Pitu Subdistrict, Ngawi Regency, focusing on information accessibility, system usage by health workers, and its impact on community knowledge regarding child nutrition and growth. This research employs a descriptive qualitative approach, with data collected through in-depth interviews with health workers, posyandu cadres, and selected parents of toddlers, as well as observations of SIMENIK usage in the field. The results are expected to provide insights into the extent to which SIMENIK can improve access to nutrition information, support health workers’ decision-making, and influence community behavior in fulfilling child nutritional needs. This study is expected to serve as a recommendation for local governments and stakeholders to strengthen the implementation of SIMENIK, enhance nutrition education quality, and accelerate stunting reduction in Pitu Subdistrict (U.N.I.C.E.F., n.d.).